The effect of lift-system airflow on the hull aerodynamics of hovercraft - Andrews, E. J. (College of Aeronautics, 1965)
A first generation of commercial amphibious hovercraft has now been operating on a scheduled basis with revenue payloads on relatively-short over-water routes. On some of these routes, open-sea conditions prevail. By and large, the degree of success attained during these operations has been encouraging. However, certain problem areas have been brought to light, one or the most important being concerned with handling qualities. As in the case of aircraft, the handling qualities of hovercraft depend heavily on stability and control characteristics. In this case, however, the problem is rather more complex being dependent on aerodynamic, hydrodynamic, and air-cushion effects. There are also important interference effects at the aero-hydro- interface. To understand the overall handling problem, each of these contributory effects must be isolated from the others, so that individual study from a stability and control viewpoint can be attempted. The task of isolation is difficult. It does not fall within the scope of full-scale testing, neither is it amenable to analysis except possibly in the case of air-cushion effects where good progress has been made using mathematical analysis. Thus it becomes essential that to study the aerodynamic and hydrodynamic effects, recourse be made to experimental testing. The National Physical Laboratory at Feltham has provided most of the effort in hydrodynamic experimentation, and the Cranfield Institute of Technology (formerly known as the College of Aeronautics) has complemented this work by undertaking the aerodynamic experimentation.